2019
DOI: 10.1371/journal.pone.0221515
|View full text |Cite
|
Sign up to set email alerts
|

An observational study using eye tracking to assess resident and senior anesthetists’ situation awareness and visual perception in postpartum hemorrhage high fidelity simulation

Abstract: Background The postpartum hemorrhage (PPH) is the leading cause of maternal mortality in the world. Human factors and especially situation awareness has primarily responsibility to explain suboptimal cares. Based on eye tracking and behavior analysis in high fidelity simulation of PPH management, the goal of this study is to identify perceptual and cognitive key parameters of the expertise. Methods Two groups of fifteen anesthetists (residents and experienced anesthetis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
(49 reference statements)
3
13
2
2
Order By: Relevance
“…Analyzing the areas of interest on the patient monitor, we found that the vital sign blood pressure received the most visual attention in both non-critical and critical scenarios. This is consistent with a recent study [11]. However, we expected the respiratory vital signs such as oxygen saturation, tidal volume, and respiratory rate to receive more visual attention.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Analyzing the areas of interest on the patient monitor, we found that the vital sign blood pressure received the most visual attention in both non-critical and critical scenarios. This is consistent with a recent study [11]. However, we expected the respiratory vital signs such as oxygen saturation, tidal volume, and respiratory rate to receive more visual attention.…”
Section: Discussionsupporting
confidence: 92%
“…Mobile eye-tracking devices have become established tools for gaining insights into cognitive processes such as visual attention, workload, con dence, and physician awareness [6][7][8]. Previous studies investigated the healthcare providers' visual attention regarding patient monitoring systems [8][9][10][11]. They found that during real anesthesia cases, healthcare professionals spent about 5% of their time observing the patient monitor [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eye tracking has also been reported as being an aid during the post scenario debriefing [21,22]. In one study [23], the performance and human factors in high-fidelity simulation of postpartum hemorrhage were analyzed by the visual behavior analysis using a standardized fixed eye tracking protocol, during viewing of a simulated video. In this study, the authors concluded suggesting a "neuroscientific approach with new technology like eye tracking to provide a new objective and more sensitive insights on human factors in simulated medical emergency situations".…”
Section: Discussionmentioning
confidence: 99%
“…They found that during real anesthesia cases, healthcare professionals spent about 5% of their time observing the patient monitor [ 8 ]. The blood pressure and heart rate seemed to be the most frequently viewed vital signs during simulated anesthesia scenarios [ 13 ], and in critical situations, anesthesiologists tend to direct more visual attention toward the patient monitor [ 14 ]. However, whether different levels of experience among healthcare providers play a role in the distribution of visual attention on the patient monitor is not yet clear [ 8 , 13 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%